Developing Occupational Safety Awareness Among Exploration Porters Through PPM Activities - Adhitya Chandra Setyawan; Gunbay (Journal of Conflict and Social Class (JCSC), 2025)
Occupational safety awareness is an essential component in supporting workplace preparedness and reducing occupational risks within mining exploration environments. Exploration porters frequently encounter hazardous working conditions, including difficult terrain, heavy equipment transportation, environmental risks, and physically demanding operational activities. This community empowerment program aimed to strengthen occupational safety awareness among exploration porters through participatory PPM activities conducted in Banyuwangi on October 22, 2025. The program employed a qualitative participatory approach involving educational workshops, practical safety demonstrations, emergency response simulations, collaborative discussions, and mentoring activities. Participants received training related to hazard identification, personal protective equipment usage, workplace communication, emergency preparedness, and safe operational behavior during exploration activities. The results demonstrated significant improvement in participants’ understanding of workplace hazards, safety procedures, risk prevention strategies, and emergency response preparedness. Participants also showed increased awareness regarding the importance of personal protective equipment and collective responsibility in maintaining workplace safety. In addition, collaborative discussions and practical simulations positively influenced participants’ communication skills, teamwork abilities, and confidence in applying occupational safety procedures during field operations. Despite challenges related to differences in educational backgrounds, traditional working habits, and limited previous safety training exposure, participatory educational methods and continuous mentoring contributed positively to strengthening safety awareness and responsible working behavior. Overall, the implementation of occupational safety training through PPM activities provided valuable opportunities for improving workplace preparedness, strengthening safety culture, and supporting sustainable community empowerment among exploration support workers in Banyuwangi.